Desarrollo de un software educativo como apoyo didáctico en el proceso de enseñanza aprendizaje de la asignatura de matemáticas, para el 7mo año de educación general básica de la escuela “John F. Kennedy” de la ciudad de Macará, periodo 2012-2013 - Jaramillo Sotomayor, Néstor Manuel (2014)
The present investigation has as theme: "DEVELOPMENT OF AN EDUCATIONAL SOFTWARE AS DIDACTIC SUPPORT IN THE LEARNING TEACHING PROCESS OF THE SUBJECT OF MATH, FOR THE 7th YEAR OF BASIC GENERAL EDUCATION OF THE "JOHN F. KENNEDY" SCHOOL MACARÁ CITY, PERIOD 2012-2013". The main objective was the creation and implementation of an educational software for the subject of Mathematics of the Seventh Year of Basic General Education, which permit to support the work of the educational one and to offer the students a new and innovative didactic resources that permit to guarantee their knowledge and interactive activities that involve to comply with the educational objectives, and the achievement of significant learnings. To reach the objectives proposed applied the descriptive, deductive, inductive methods and the statistical model, as well as, the survey and interview and instruments as investigative techniques, for the harvesting of information, with the participation of the students and educational of the educational institution, verifying the lack of didactic resources. The employed methodology for the construction of the application is called "Dynamic Methodology of Development of Educational Software". As results of the present investigation was identified that teachers have knowledge the (100%) and disposition to use the educational software, besides they expressed that the block 4 (50%) and 5 (50%) are the greater complexity of comprehension for the students. Before this situation develops the educational software with multimedia contained and practical activities to fortify the educational process, where the student will be able to feedback and to generate his own knowledge.